Agrupamento de municípios do médio Paranapanema de acordo com a produção agropecuária local: Uma abordagem multivariada - Bianchi, Vinícius Rafael [UNESP]; de Oliveira, Sandra Cristina [UNESP]; Pinto, Leonardo de Barros [UNESP]; Andreoli, Ana Cláudia [UNESP]; Garnica, Guilherme Besse [UNESP] (My University, 2016)
Agribusiness is one of the most important activities of the national economy and the state of São Paulo, with production diversity, forms of production and social formation. The objective of this study was to identify clusters or groupings of municipalities in the Middle Paranapanema, in the state of Sao Paulo, Brazil, according to their agricultural production and acreage registered by the Institute of Agricultural Economics in 2013, seeking to evaluate which products, among those who stood out in 2013 in that region (sugar cane, cassava, corn and soybeans), have contributed to the socioeconomic development of each cluster formed in the region.
Grouping of municipalities the middle Paranapanema according to the local agricultural production: A multivariate approach
Keywords: Agribusiness; Cluster Analysis; Socioeconomic development